The greater role of Southern Ocean warming compared to Arctic Ocean warming in shifting future tropical rainfall patterns - Hyein Jeong; Hyo-Seok Park; Sarah M. Kang; Eui-Seok Chung (Nature Communications)
Abstract The recent rapid decline in Antarctic sea ice highlights the need to understand whether rising Southern Ocean temperatures have an influence on global climate. While Arctic warming has been extensively studied, the importance of Southern Ocean warming is emerging only now. Here, using multi-model simulations, we show that over 1.5 °C of Southern Ocean surface warming can offset the projected northward shift in tropical zonal-mean precipitation by the mid-21st century, driven by stronger northern high-latitude warming under rising greenhouse gas concentrations. SST nudging experiments suggest that a 1.0 °C warming in the Southern Ocean could impact tropical precipitation as significantly as a 1.5 °C warming in the Arctic. Regionally, Southern Ocean warming increases rainfall in northeastern Brazil while heightening drought risks in the Sahel. These effects are comparable to, or slightly more pronounced than, those caused by a weakening Atlantic Meridional Overturning Circulation and the associated development of the North Atlantic warming hole. Thus, Southern Ocean warming may play a more crucial role than Arctic warming in shaping tropical climate patterns in the coming decades.